2017
DOI: 10.1002/adma.201702983
|View full text |Cite
|
Sign up to set email alerts
|

Smart Bioinspired Nanochannels and their Applications in Energy‐Conversion Systems

Abstract: materials. For example, nanochannels fab ricated in elastic materials can respond to an applied pressure, [4] and conical nanochannels in poly(ethylene tereph thalate) (PET) membranes can respond to pH. [5] Thus, it is convenient to achieve simple responsive properties by directly using responsive materials to construct the nano channels. The second route is an indirect method, where functional molecules and materials are modified onto the inner surfaces of nanochannels. This method can change the physical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 85 publications
0
47
0
Order By: Relevance
“…In this respect, the emerging bioinspired nanofluidic heterogeneous membranes that are constructed by the hybridization of two monolayer porous membranes have shown unprecedented superiority [16][17][18][19][20] . The synergistic effect between the two layers with inherent asymmetric structure, charge, and wettability would contribute to novel ionic transport properties such as ionic diode effect [21][22][23] .…”
mentioning
confidence: 99%
“…In this respect, the emerging bioinspired nanofluidic heterogeneous membranes that are constructed by the hybridization of two monolayer porous membranes have shown unprecedented superiority [16][17][18][19][20] . The synergistic effect between the two layers with inherent asymmetric structure, charge, and wettability would contribute to novel ionic transport properties such as ionic diode effect [21][22][23] .…”
mentioning
confidence: 99%
“…Typically, the open circuit voltage reached tens of mV to 300 mV, and the open circuit current density reached 3 A m −2 . The nanochannels were placed between artificial river water (0.01 m NaCl) and artificial seawater (0.5 m NaCl), and the power generated was used to supply an electrical load . The power density obtained was shown in Figure f. As the load resistance increased, the current density decreased and the output power density reached a maximum of about 0.1 W m −2 , with a resistance of about 100 kΩ.…”
Section: Resultsmentioning
confidence: 99%
“…Ty pically,t he open circuit voltage reached tens of mV to 300 mV,a nd the open circuit current density reached 3Am À2 .T he nanochannels were placed between artificial river water (0.01m NaCl) and artificial seawater (0.5 m NaCl), and the power generated was used to supply an electrical load. [45] Thep ower density obtained was shown in Figure 5f.A st he load resistance increased, the current density decreased and the output power density reached am aximum of about 0.1 Wm À2 ,w ith aresistance of about 100 kW.These results demonstrated that the gold nanoarray heteromembrane had an energy conversion capacity,s uggesting new directions for future research into gold nanoarray heteromembranes.…”
Section: Angewandte Chemiementioning
confidence: 99%